Impacts of 3Li2O-2GeO2 melt on fabrication and electrical performance of novel LLZTO@Li4GeO4/Li2O composite electrolytes. Issue 5 (May 2022) - Wang, Ce; Liu, Zhan-Guo; Lin, Pan-Pan; Xu, Xiao; Lu, Fu-Gang; Xu, Jiu-Jie; Shi, Yu-Hao; He, Peng; Lin, Tie-Song
Highlights: Novel LLZTO@Li4 GeO4 /Li2 O composite electrolytes are successfully produced. Compact connections among LLZTO grains are fabricated by LGO1.5 additive. LGO1.5 additive acts as a bridge to enhance Li + conduction in grain boundary domains. Prominent promotion for structure and properties of garnet electrolytes are achieved. Impacts and crucial roles of LGO1.5 additive are revealed. Abstract: Novel LLZTO@Li4 GeO4 /Li2 O composite electrolytes have been successfully produced through liquid sintering Li6.4 La3 Zr1.4 Ta0.6 O12 via the 3Li2 O-2GeO2 (LGO1.5) additive at 1140 °C for 3 h in air atmosphere. The Li-Ge-O additive performs a prominent role in fabricating compact connections among LLZTO grains and accelerating their densification procedure. Moreover, the additive acts as a bridge to promote Li + transportation in the grain boundary domains. Consecutive Li + conduction pathways are constructed inside the ceramics correspondingly. A considerably enhancement for the electrical performance of the garnet-type electrolytes is realized. The composite electrolyte with 2wt% LGO1.5 exhibits a high ionic conductivity of 5.57 × 10 −4 S·cm ‒1 at 25 °C, the relative density of which reaches 95.8%. It is also capable of withstanding a high voltage up to 6 V (vs. Li/Li + ) and a large critical current density of 0.65 mA·cm ‒2 .